Ready player one - Cline, Ernest (New York : Broadway Paperbacks, 2011)
Immersing himself in a mid-twenty-first-century technological virtual utopia to escape an ugly real world of famine, poverty, and disease, Wade Watts joins an increasingly violent effort to solve a series of puzzles by the virtual world's creator.
Keywords: Regression (Civilization) -- Fiction; Virtual reality -- Fiction; Utopias -- Fiction; Puzzles -- Fiction; Fantasy fiction